The policy determinants of investment in tertiary education - Oliveira Martins, Joaquim (OECD Publishing, 2009)
The purpose of this article is to discuss how policies can affect investment in tertiary education in ways that would eliminate some of the perceived shortcomings of existing systems, while preserving or (preferably) enhancing equality of access to higher education. To this end, the analysis focuses on the institutional set-up of tertiary education that provides incentives for supplying quality educational services; the private returns from higher education which act to attract prospective students; and, individual funding mechanisms to help overcome the liquidity constraints that may restrict participation in higher education. These mechanisms should also be designed so as to prevent uncertainty about future incomes from unduly deterring investment in tertiary studies by risk-averse individuals. Joaquim Oliveira Martins, Romina Boarini, Hubert Strauss and Christine de la Maisonneuve